Whatever it takes: What's the impact of a major nonconventional monetary policy intervention? - Carlo Alcaraz; Stijn Claessens; Gabriel Cuadra; David Marqués Ibá\~nez; Horacio Sapriza (European Central Bank (ECB), 2019)
We assess how a major, unconventional central bank intervention, Draghi's "whatever it takes" speech, affected lending conditions. Similar to other large interventions, it responded to adverse financial and macroeconomic developments that also influenced the supply and demand for credit. We avoid such endogeneity concerns by focusing on a third country and comparing lending conditions by euro area and other banks to the same borrower. We show that the intervention reversed prior risk-taking - in volume, price, and loan credit ratings - by subsidiaries of euro area banks relative to local and other foreign banks. Our results document a new effect of large central banks' interventions and are robust along many dimensions.
Keywords: E51; G21; F34; 330; Unconventional monetary policy; credit conditions; spillovers